2023
DOI: 10.1039/d3tc02842a
|View full text |Cite
|
Sign up to set email alerts
|

High Seebeck coefficient from isolated oligo-phenyl arrays on single layered graphene via stepwise assembly

Xintai Wang,
Ali Ismael,
Bashayr Alanazi
et al.

Abstract: Organic thin films composed of highly ordered molecular arrays have great potential for thermoelectric energy harvesting. Molecular arrays bound to graphene substrates via non-covalent interactions have shown better thermoelectric behavior...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…5,6,41,52 Consequently, this molecular junction design with graphene doping could exhibit favorable thermoelectric properties, given that the thermoelectric power factor is proportional to S 2 and G. [53][54][55] In the case of C 6 NH 2 -doped systems, the conductance shift in both SAM 1 and SAM 2 was less significant compared to those doped with PBase. Despite this, C 6 NH 2 's large HOMO-LUMO gap and its propensity to form high-quality densely packed monolayers on graphene 11,56 indicate its potential application as a dielectric layer for controlling the Fermi level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,41,52 Consequently, this molecular junction design with graphene doping could exhibit favorable thermoelectric properties, given that the thermoelectric power factor is proportional to S 2 and G. [53][54][55] In the case of C 6 NH 2 -doped systems, the conductance shift in both SAM 1 and SAM 2 was less significant compared to those doped with PBase. Despite this, C 6 NH 2 's large HOMO-LUMO gap and its propensity to form high-quality densely packed monolayers on graphene 11,56 indicate its potential application as a dielectric layer for controlling the Fermi level.…”
mentioning
confidence: 99%
“…53–55 In the case of C 6 NH 2 -doped systems, the conductance shift in both SAM 1 and SAM 2 was less significant compared to those doped with PBase. Despite this, C 6 NH 2 's large HOMO–LUMO gap and its propensity to form high-quality densely packed monolayers on graphene 11,56 indicate its potential application as a dielectric layer for controlling the Fermi level.…”
mentioning
confidence: 99%
“…[1][2][3] To realize this target, various strategies have been developed to measure the conductance, current-voltage characteristics, inelastic electron tunneling spectra, transition voltage spectra (TVS), and current-induced local heating of single molecules located between two electrodes. [4][5][6][7] Theories of electron transport in singlemolecule junctions are built on the concept that electrons passing through a molecule from a source electrode to a drain electrode are phase coherent and that the energy E of the electron does not change during the passage. [8][9][10] Consequently, if the source-drain voltage is small, the electrical conductance G of the molecular junction is given by the Landauer formula G = G 0 T(E F ), where G 0 is the quantum of conductance and T(E F ) is the transmission coefficient, evaluated at the Fermi energy E F of the electrodes.…”
mentioning
confidence: 99%
“…As an illustration, π-stacks of single molecules have been structured by employing guest aromatic molecules into host aromatic cages [23] or by covalently linking aromatics using strained paracyclophane backbones [13]. Nonetheless, a full control over the stacking distribution in the π-stacks has not been achieved because of the random molecular orientation [17][18][19][23][24][25]. The same work [16] of the π-stacks demonstrated that the molecular orientation of the π-stacks was not controlled on a gold surface.…”
Section: Introductionmentioning
confidence: 99%